"There's always an option" : Collaborative Writing of Multilingual Interactive Fanfiction in a Foreign Language Class. (28th January 2021) - Cornillie, Frederik; Bündgens-Kosten, Judith; Sauro, Shannon; Van der Veken, Joeri
Abstract : In the digital wilds, thriving storytelling practices (often in transcultural and multilingual contexts) share with Maker culture a belief in learning through doing, bricolage, collaboration, and playfulness. Key examples are fanfiction, a form of creative writing that transforms popular media in some way, and interactive fiction, a form of nonlinear narrative that verges on the world of gaming. This paper documents a pedagogical intervention carried out within the FanTALES project, which leverages creative writing and meaning-making practices from the digital wilds, in order to develop teaching and learning activities that engage secondary school learners in the writing of multilingual interactive fanfiction. Adolescent learners of English as a foreign language (N=21) wrote multilingual interactive fanfiction based on the digital game series Assassin's Creed. Qualitative content analysis of focus groups with these learners suggests that they experienced intrinsic motivation and developed skills in language and storytelling as well as transversal competences. They also dealt with a lowered sense of autonomy due to the open-endedness of the tasks, and struggled with a lack of sufficient knowledge about storytelling practices and the source text, as well as with project management. Potential improvements for the pedagogical implementation include more scaffolding of the tasks, and better integration with curriculum and assessment.